Self-Confidence and Arabic Language Achievement: The Mediating Effect of Vocabulary Mastery - M Kholis Amrullah; Umar Najih Zein; Wisatrat Wilailak; Ridha Fadillah (UIN ANTASARI, 2025)
This study tested the influence of confidence on the Arabic Semester Final Assessment through vocabulary mastery in class X students of MA Walisongo Sukajadi. Highlighting the importance of Arabic language mastery and the affective role of self-confidence, this study aims to analyze the direct and indirect influence of confidence on vocabulary-mediated Arabic PAS. Using a quantitative approach with simple path analysis, 101 students were used as purposive sampling samples. Data were collected from confidence questionnaires, vocabulary tests, and PAS scores; The instrument has been valid and reliable. The results of the analysis showed that confidence did not have a significant effect on vocabulary mastery (p=0,117). In addition, neither self-confidence (p=0,418) nor vocabulary mastery (p=0,634) had a significant influence on Arabic PAS. It was concluded that there was no significant mediating evidence of vocabulary mastery in the relationship between self-confidence and the Arabic Semester Final Assessment in this sample.